Chloroplast thylakoid ascorbate peroxidase PtotAPX plays a key role in chloroplast development by decreasing hydrogen peroxide in Populus tomentosa. (21st April 2021) - Li, Conghui; Liu, Yadi; Liu, Xiatong; Mai, Keith Ka Ki; Li, Jiaxin; Guo, Xiaorui; Zhang, Chong; Li, Hui; Kang, Byung-Ho; Hwang, Inhwan; Lu, Hai
Abstract : The callus derived from leaf tissue of Populus tomentosa can be used to study chloroplast development and PtotAPX-mediated removal of ROS is critical for chloroplast development from proplastids. Abstract: Chloroplast development is a complex process that is critical to the growth and development of plants. However, the detailed mechanism of chloroplast development in woody plants remains unclear. In this study, we showed that chloroplasts with elaborate thylakoids could develop from proplastids in the cells of calli derived from leaf tissues of Populus tomentosa upon exposure to light. Chloroplast development was confirmed at the molecular and cellular levels. Transcriptome analysis revealed that genes related to photoreceptors and photosynthesis were significantly up-regulated during chloroplast development in a time-dependent manner. In light-induced chloroplast development, a key process was the removal of hydrogen peroxide, in which thylakoid-localized PtotAPX played a major role; light-induced chloroplast development was enhanced in PtotAPX -overexpressing transgenic P. tomentosa callus with lower levels of hydrogen peroxide, but was suppressed in PtotAPX antisense transgenic callus with higher levels of hydrogen peroxide. Moreover, the suppression of light-induced chloroplast development in PtotAPX antisense transgenic callus was relieved by the exogenous reactive oxygen species scavenging agent N, N′-dimethylthiourea (DMTU). Based on these results, we propose that PtotAPX-mediated removal of reactive oxygen species plays a key role in chloroplast development from proplastids upon exposure to light in P. tomentosa .